The Impact of Organizational Climate on Organizational Conflict in ALmanaseer Industrial Complex - Tommalieh, Laith Wael; Al- Saed, Rashad Mohammed (Journal of Economic, Administrative and Legal Sciences, 2020)
This study aimed to measure the impact of organizational climate on organizational conflict in Almanaseer Industrial Complex. The study used descriptive and analytical methodology to deal with and classifying data, by designed and developed a questionnaire to be a study tool, in order to collect data from a study sample, then analyzed through the statistical Program Statistical Package for the Social Sciences (SPSS V.23). This study reached a number of results, the most important of which are: The study found that there is an impact of organizational climate dimensions (Leadership style, Communications, Participation in Decision Making) in organizational conflict in all if its dimensions (Role Ambiguity, Poor Cooperation, Individual Differences) at Almanaseer Industrial Complex. The study propose a few recommendations for Almanaseer Industrial Complex; Develop the current organizational structure in Almanaseer Industrial Complex to be a stand- alone integrated unit among all departments, which may contribute to meet and facilitate the needs of workers in the complex.